Creating a Model of Special Educational Settings for Disabled Students in Higher Education - Rubtsov V.V; Vasina L.G; Kuravsky L. S.; Sokolov V.V (Moscow State University of Psychology and Education, 2017)
The authors present their experience of designing a model of special educational settings for students with visual impairments enrolled in bachelor's programmes in Mathematical Support and Administration of Information Systems and Applied Computer Science. The authors discuss requirements for career guidance, application for university admission, academic and psychological support in students with visual impairments and review the system of employment assistance for graduate students with disabilities. The outcomes of the research indicate that project-based learning, active involvement in research and participation in finding solutions to relevant practical tasks promotes high quality training in disabled students.